Metastasis of esophageal squamous cell carcinoma to the thyroid gland with widespread nodal involvement: A case report - Zhang, Xing (World J Clin Cases, 2020)
BACKGROUND: Esophageal cancer is one of the most common causes of cancer-related death. Some patients with esophageal cancer have distant metastases at the time of diagnosis, but metastasis to the thyroid gland (MTG) and multifocal thyroid lesions alone are extremely rare. CASE SUMMARY: In this case report, we present a case of a 69-year-old male with esophageal MTG. The patient visited our hospital for a routine body check-up, which revealed multifocal nodules in his thyroid lobes and enlarged cervical lymph nodes. A fine needle aspiration biopsy showed malignancies in both thyroid lesions and lymph nodes. The patient was initially diagnosed with primary bilateral thyroid cancer that spread to his lymph nodes, and a total thyroidectomy was performed. The histology showed MTG and therefore, a diagnostic work-up was implemented to determine the primary tumor. A fluorine-18-deoxyglucose positron emission tomography scan showed that the lower part of the esophagus and the lymph nodes in the neck, chest, and abdomen were involved. An esophagogastroscopy and corresponding pathology revealed distal esophageal squamous cell carcinoma. The esophageal MTG diagnosis was confirmed with pathological immunohistochemistry. CONCLUSION: This case report highlights the difficulty in diagnosing esophageal MTG. Patients may have no malignancy history and be asymptomatic. Further diagnostic procedures are necessary after MTG is confirmed by cytology or histology, and the final diagnosis should be made according to the identification of the primary malignancy combined with pathological immunohistochemistry findings.